Canberra Times index 1926 - 1974. - Heraldry & Genealogy Society of Canberra ([Canberra : Heraldry & Genealogy Society of Canberra, 2004)
An index of the death, funeral and in memoriam notices published in the Canberra Times from 3 September 1926 to 31 December 1974.
Title from disc.
System requirements: IBM PC or compatible ; CD-ROM drive ; Microsoft Excel.
Digital content preserved
Keywords: Canberra times -- Indexes; Canberra (A.C.T.) -- Genealogy -- Indexes